Linguagem no Ensino Religioso chaves de leitura para compreender a influência do pensamento antropológico de Wolfgang Gruen chaves de leitura para compreender a influência do pensamento antropológico de Wolfgang Gruen - Siqueira, Giseli do Prado (2022)
Religious Education, a legally recognized curricular component, has gone through different nomenclatures and systematizations in Brazil. From the confessional and catechetical conception, through the formation of Christian values, to the paradigmatic change proposed by Wolfgang Gruen through the use of language, methodology appropriate to the school environment and the training of educators. Gruen emphasized liberation through language, instigating us to ask: what are the keys to understanding the influence of Wolfgang Gruen anthropological thought in the definition of the most appropriate language for Religious Education? We opted for a bibliographical research, going through the author's academic production in order to understand what this language is. This investigation found that the definition of religiosity as an object of knowledge of Religious Education, in the thought of Wolfgang Gruen, defined the language of religiosity, that is, the language of outsiders, as the most appropriate for the school environment.
Keywords: Ensino Religioso; Linguagem; Religiosidade; Wolfgang Gruen